Karakter Kejujuran Pada Pedagang Dalam Transaksi Jual Beli Di Pasar Tradisional(Studi Kasus pada Pedagang di Pasar Sayur Kabupaten Magetan) - Fauziah, Farah Dhiba, Dra. Hj. Sri Arfiah, SH, MPd (2016)
The purpose of this study is to describe the application, and sousi constraints of the application code on the honesty of traders in buying and selling on Vegetable Market Magetan. This type of research is qualitative. Data collection techniques used in this study is observation, interview, and documentation. This study uses triangulation triangulation of data sources and data collection techniques. Data analysis technique used is interactive analysis. It can be concluded that the application of honesty characters performed by traders is through equalizing the selling price of all kinds of products, goods and services, awareness about the importance of honesty, socialization or appeal to do honest. as well as sanctions for breaking the rules. The obstacles are still there are traders who say not honest about the quality of goods and price, and cheat by manipulating the weighing device. Dishonest acts also performed by officers of retribution. Officers collector levy perform illegal fees by raising the tariff is quite high and very burdensome merchants. The solution is the provision of strict sanctions for merchants and officers levy.